Biodegradable, thermoplastic polyurethane grafts for small diameter vascular replacements. (1st January 2015) - Bergmeister, Helga; Seyidova, Nargiz; Schreiber, Catharina; Strobl, Magdalena; Grasl, Christian; Walter, Ingrid; Messner, Barbara; Baudis, Stefan; Fröhlich, Sophie; Marchetti-Deschmann, Martina; Griesser, Markus; di Franco, Matt; et al.
Graphical abstract: Abstract: Biodegradable vascular grafts with sufficient in vivo performance would be more advantageous than permanent non-degradable prostheses. These constructs would be continuously replaced by host tissue, leading to an endogenous functional implant which would adapt to the need of the patient and exhibit only limited risk of microbiological graft contamination. Adequate biomechanical strength and a wall structure which promotes rapid host remodeling are prerequisites for biodegradable approaches. Current approaches often reveal limited tensile strength and therefore require thicker or reinforced graft walls. In this study we investigated the in vitro and in vivo biocompatibility of thin host-vessel-matched grafts ( n = 34) formed from hard-block biodegradable thermoplastic polyurethane (TPU). Expanded polytetrafluoroethylene (ePTFE) conduits ( n = 34) served as control grafts. Grafts were analyzed by various techniques after retrieval at different time points (1 week; 1, 6, 12 months). TPU grafts showed significantly increased endothelial cell proliferation in vitro ( P < 0.001). Population by host cells increased significantly in the TPU conduits within 1 month of implantation ( P = 0.01). After long-term implantation, TPU implants showed 100% patency (ePTFE: 93%) with no signs of aneurysmal dilatation. Substantial remodeling of the degradable grafts was observed but varied between subjects. Intimal hyperplasia was limited to ePTFE conduits (29%). Thin-walled TPU grafts offer a new and desirable form of biodegradable vascular implant. Degradable grafts showed equivalent long-term performance characteristics compared to the clinically used, non-degradable material with improvements in intimal hyperplasia and ingrowth of host cells.